Challenges of Reading Coordinators in the Implementation of School-Based Reading Programs Among Rural and Urban Schools in Davao Del Sur (American Journal of Multidisciplinary Research and Innovation, 2025)
Reading comprehension is one of the primary issues we have been dealing with recently, for which we have not discovered a solution but must. Reading comprehension issues are very prevalent in Davao del Sur. This qualitative study examines the challenges reading coordinators encounter in urban and rural areas while implementing reading programs at the primary education level in Davao del Sur, Philippines. Six participants were chosen through purposive sampling, with equal representation from urban and rural schools. In-depth, face-to-face interviews provided insights into their experiences. The findings reveal that despite having sufficient resources, urban coordinators need help motivating teachers and tailoring strategies to meet diverse student needs. Conversely, rural coordinators face more significant challenges, including limited resources, difficulties recruiting qualified teachers, and a need for more professional development opportunities. The study underscores the importance of improving resources, enhancing professional development, and fostering more vital collaboration between teachers and parents in urban and rural settings.